USP33-mediated stabilization of c-Myc drives glycolytic reprogramming and promotes ovarian cancer progression - Chen, Dejia; Zhao, Yue; Zhang, Xiaobo; Shi, Xiaocheng; Liu, Yiming; Lou, Ge (Biochimica et biophysica acta. General subjects, 2025)
Ovarian cancer (OC) is one of the most lethal gynecological malignancies, characterized by late-stage presentation, high recurrence rates, and a lack of effective early diagnostic markers. Recent evidence suggests that deubiquitinating enzymes (DUBs) play pivotal roles in tumor development and metabolic reprogramming. Here, we identify and characterize the function of the deubiquitinase USP33 in regulating c-Myc stability and glycolytic metabolism in OC. Through quantitative PCR (qPCR) and Western blot analyses, we show that USP33 is significantly upregulated in both OC tissues and cell lines compared to normal controls. Functional assays reveal that USP33 knockdown markedly inhibits cell proliferation, migration, and invasion while promoting apoptosis. Metabolically, USP33 silencing reduces glucose uptake, lactate production, and the extracellular acidification rate, consistent with downregulation of key glycolytic enzymes (LDHA, GLUT1, and PKM2). Mechanistically, co-immunoprecipitation and ubiquitination assays demonstrate that USP33 interacts with and deubiquitinates c-Myc at K48-linked chains, thereby stabilizing c-Myc protein levels and enhancing its transcriptional activity. Moreover, c-Myc overexpression rescues the inhibitory effects of USP33 knockdown on both glycolysis and malignant phenotypes. Clinically, high USP33 expression correlates with poor prognosis, suggesting that the USP33–c-Myc axis may serve as both a prognostic biomarker and a potential therapeutic target. Taken together, our findings highlight a critical role for USP33 in OC pathogenesis by mediating c-Myc-driven glycolytic reprogramming, and they provide new insights for developing targeted treatment strategies aimed at disrupting this pathway. •USP33 is upregulated in ovarian cancer: Significantly higher expression is observed in tumor tissues and cell lines compared to normal controls.•Promotes malignancy: USP33 knockdown inhibits proliferation, migration, and invasion while inducing apoptosis.•Enhances glycolysis: USP33 stabilizes c-Myc, upregulating glycolytic enzymes (LDHA, GLUT1, PKM2) to increase glycolytic flux.•Deubiquitinates c-Myc: Removes K48-linked ubiquitin chains, preventing degradation and enhancing transcriptional activity.•Clinical relevance: High USP33 levels predict poor prognosis, indicating USP33/c-Myc as a potential therapeutic and diagnostic target.